(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
In realizing the objectives of the development program in each institution it takes a managerial pattern in the management of development and other governmental programs to be perceived and enjoyed by the community. The use of village funds is prioritized in village development. One of the most important things needed is the wisdom of the village head to direct and guide the community to jointly implement the development program. The purpose of this research is to know how the Management Of Village Funds In Development In Paslaten Village Langowan West District Minahasa Regency. The research methods used in this study are qualitative methods. The informant in the research is a person who can provide information about the situation and background conditions of research. The focus of research is seen from the indicator according to George Terry, which is planning, organizing, mobilization and controlling. Data collection techniques through observation, interviews, and documentation. The results showed that the Management Of Village Funds In Development In Paslaten Village Langowan West District Minahasa Regency in the management of village funds is not done transparently or openly to every community even a lot of issues Community that the management of village funds in the use of village funds is not suitable for it. Keywords : Management, Village Funds, Development.